Operant Discriminative Learning and Evidence of Subtelencephalic Plastic Changes After Long-Term Detelencephalation in Pigeons - S. M. Cerutti; S. Diaz-Cintra; L. Cintra; E. A. M. Ferrari (Neural Plasticity)
We analyzed operant discrimination in detelencephalated pigeons and neuroanatomical substrates after long-term detelencephalation. In Experiment I, experimental pigeons with massive telencephalic ablation and control pigeons were conditioned to key peck for food. Successive discrimination was made under alternating red (variable-ratio reinforcement) and yellow (extinction) lights in one key of the chamber. These relations were interchanged during reversal discrimination. The sessions were run until steady-state rates were achieved. Experiment II analyzed the morphology of the nucleus rotundus and optic tectum in long-term detelencephalated and control birds, using a Klüver-Barrera staining and image analyzer system. Detelencephalated birds had more training sessions for response shaping and steady-state behavior (p<0.001), higher red key peck rates during discrimination (p<0.01), and reversal discrimination indexes around 0.50. Morphometric analysis revealed a decreased number of neurons and increased vascularity, associated with increases in the perimeter (p<0.001) in the nucleus rotundus. In the optic tectum, increases in the perimeter (p<0.05)